Bioactive TiO2 Fibers Prepared by Solution Blow Spinning: A Promising Approach for Microbial Control - Tiago Cesar Gimenes; Guilherme Schiavão Padovani; Eloisa Aparecida Carvalho Silva; Higor de Souza Silva; Gabriel Menegolo De Castro Meira; Alex Otávio Sanches; José Antônio Malmonge; Alexandre J. Gualdi; Fernando R. de Paula (Materials Research, 2024)
PEO/TiP fibers were obtained using the Solution Blow Spinning (SBS) apparatus and heat treated to produce TiO2 fibers. The morphological and structural characteristics were assessed using SEM and X-ray diffraction. The fibers, with a thickness of 12 μm, showed a change in crystalline structure with heat treatment. At temperatures as low as 800 °C, only the anatase phase was identified, while at 900 °C, both anatase and rutile phases coexisted. The addition of TiP to the polymer matrix reduced the initial breakdown temperature, and the DSC curves showed exothermic peaks due to the amorphous phase transition to TiO2/anatase. The fibers' photocatalytic capacity was tested, revealing that TiO2-fibers in the anatase phase achieved 97% degradation of Rhodamine-B dye in 40 minutes. The study found that the biocide efficacy of TiO2-fibers depends on their heat treatment. Fibers with anatase/rutile or pure rutile phases did not show significant efficiency. However, fibers treated at 600°C with pure anatase phase were more effective in eliminating E. coli and total coliforms. Finally, we can state that the TiO2 fibers obtained in this work using the SBS technique can be used to produce filters to purify water contaminated by pathogens dangerous to human health or even to purify the air.